(untitled) (Revista Brasileira Multidisciplinar, 2015)
This text recalls the history of Tamoio Mill and of the social group made up of their workers and residents in the period from 1917 to 1969. First of all, it is a story of men, women and children who worked and lived there. More than the rescue of the history of the company, it tries to retell, in the subjects’ voice, their experiences and memories, a story of life and work. A story that was marked in body and soul of these hard-working people who made the Tamoio Mill an important legacy to Araraquara.